PENERAPAN MODEL PETA PIKIRAN (MIND MAPPING) UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IVB SD NEGERI 007 BANGKINANG - Iis Aprinawati (FIP Unimed, 2017)
ABSTRACTThis study aims to describe the improvement of students' writing skills narrative grade IVB SDN 007 Bangkinang. The subjects of this study were the students of the IVB class which amounted to 22 people. The data collection techniques used in this research were documentation, observation, and test. Based on the results of this study can be concluded that writing the narrative essay of students is good, from 22 students only 17 students or 77.27% who achieve mastery individually. The result of writing the narrative essay of students in cycle II is also quite good with an average of 82.54 and from 22 students there are 19 students or 86.36% who achieve mastery individually. Thus it can be concluded that the application of Mind Mapping model can improve can improve the writing skills skill of students' narrative class IVB SDN 007 Bangkinang.Keyword : Model Mind Mapping, Result Of Skill Write, Composition Of Narasi